Time analysis for the IAAF World Championships London 2017 10.000 m men's - Hanley, B.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
The men`s 10,000 m final, the first of the 2017 Championships, took place in the late evening on August 4th. The race was tightly contested, with local favourite and multiple global champion Farah winning by less than half a second from the fast-finishing Cheptegei. Farah`s winning time was just over three seconds slower than the Championship Record, and the fast nature of the race was highlighted by 12 personal best times (including two national records), with eight others recording season`s bests (including Farah`s world leading time). Nzikwinkunda was unusual in that he had no personal best for the distance recorded, but did qualify as one of the top 15 finishers in the 2017 World Cross Country Championships. The results for all finishers are shown. (Attention! registration on the IAAF site is required for downloading)